Insertion/deletion polymorphisms in the ΔNp63 promoter are a risk factor for bladder exstrophy epispadias complex. - Simon Wilkins; Ke Wei Zhang; Istiak Mahfuz; Renaud Quantin; Nancy D'Cruz; John Hutson; Michael Ee; Darius Bagli; Karen Aitken; Fion Nga-Yin Fong; Patrick Kwok-Shing Ng; Stephen Kwok-Wing Tsui; et al. (PLoS Genetics)
Bladder exstrophy epispadias complex (BEEC) is a severe congenital anomaly; however, the genetic and molecular mechanisms underlying the formation of BEEC remain unclear. TP63, a member of TP53 tumor suppressor gene family, is expressed in bladder urothelium and skin over the external genitalia during mammalian development. It plays a role in bladder development. We have previously shown that p63(-/-) mouse embryos developed a bladder exstrophy phenotype identical to human BEEC. We hypothesised that TP63 is involved in human BEEC pathogenesis. RNA was extracted from BEEC foreskin specimens and, as in mice, ΔNp63 was the predominant p63 isoform. ΔNp63 expression in the foreskin and bladder epithelium of BEEC patients was reduced. DNA was sequenced from 163 BEEC patients and 285 ethnicity-matched controls. No exon mutations were detected. Sequencing of the ΔNp63 promoter showed 7 single nucleotide polymorphisms and 4 insertion/deletion (indel) polymorphisms. Indel polymorphisms were associated with an increased risk of BEEC. Significantly the sites of indel polymorphisms differed between Caucasian and non-Caucasian populations. A 12-base-pair deletion was associated with an increased risk with only Caucasian patients (p = 0.0052 Odds Ratio (OR) = 18.33), whereas a 4-base-pair insertion was only associated with non-Caucasian patients (p = 0.0259 OR = 4.583). We found a consistent and statistically significant reduction in transcriptional efficiencies of the promoter sequences containing indel polymorphisms in luciferase assays. These findings suggest that indel polymorphisms of the ΔNp63 promoter lead to a reduction in p63 expression, which could lead to BEEC.